Proliferation and odontogenic differentiation of human umbilical cord mesenchymal stem cells and human dental pulp cells co-cultured in hydrogel. (January 2020) - Huang, Chunyang; Bao, Lirong; Lin, Tian; Lu, Yanling; Wu, Yu
Graphical abstract: Highlights: Scaffold materials play an important role in regenerative medicine research. Hydrogel scaffolds supported the hUCMSCs and hDPCs growth and proliferation. 3D co-culture systemexhibitedmore proliferative potentialthan cell-monoculture. Abstract: Objective: The aim of this study was to evaluate the proliferation and odontogenic differentiation of human dental pulp cells (hDPCs) and human umbilical cord mesenchymal stem cells (hUCMSCs) in three-dimensional co-culture system which was established with the help of bone morphogenetic protein-2 (BMP-2) and hydrogel. Methods: hDPCs and hUCMSCs were cultured in different concentrations of hydrogel to explore the more suitable concentrations for subsequent experiments. hUCMSCs and hDPCs induced by BMP-2 were co-cultured in the hydrogel. MTT assay was used to measure the cell viability. The differentiation into odontoblast-like cells were measured by the mRNA expression of dentin salivary phosphoprotein (DSPP), dentin matrix protein-1 (DMP-1), alkaline phosphatase and osteocalcin. Alizarin red staining was performed for the formation of mineralized nodules. Results: hUCMSCs and hDPCs could grow and proliferate in hydrogel scaffold. The growth rate of cells in lower concentrations hydrogels were higher than that of high concentrations hydrogels (P < 0.05). The study showed that 0.25% hydrogel scaffold was more suitable for subsequent experiments than other groups. Compared with hUCMSCs-monoculture and hDPCs-monoculture, the co-culture groups exhibited more proliferative potential, alkaline phosphatase activity and mineralization nodule formation (P < 0.05). The mRNA expression in co-culture groups were higher than that of hUCMSCs-monoculture, closed to or even higher than that of hDPCs-monoculture. Conclusion: 0.25% hydrogel was the suitable concentration in co-culture system for subsequent experiments. The co-culture groups had stronger abilities of odontoblastic differentiation and mineralization than cells-monoculture groups, indicated that the co-culture conditions could regulate cell proliferation and differentiation within a certain range.